Biblical Entrepreneurship: Dasar dalam Memulai Bisnis bagi Anak Muda Kristen Usia 18-25 Tahun - Daniel Martin Tamera; Angelica Liveani Rivela; Sugeng Santoso; Erastus Sabdono; Anwar Three Millenium Waruwu (KHARISMATA: Jurnal Teologi Pantekosta, 2024)
The problem of fraud and crime in entrepreneurial practice is rampant in the business world, behaviorally or characteristically, so damaged and said to violate morals and also ethics in business. Therefore, this study discusses the importance of entrepreneurship for young Christians from a biblical perspective and its implications for business practices. In this article, the researcher uses a qualitative method through literature sources such as books, journal articles, the Bible, and internet media that can be accounted for as well as in-depth analysis. Furthermore, with a focus on biblical values, the research highlights the importance of supporting young people to become entrepreneurs. The results of the study highlight the essence of entrepreneurship from a biblical perspective that emphasizes character building, spiritual growth, and responsibility. In addition, Entrepreneurship is seen as a calling to serve and bless others, as well as understanding the principles of Biblical Entrepreneurship to realize God's Great Commission in Christian youth business.Permasalahan kecurangan dan kejahatan dalam praktek berwirausaha marak terjadi di dunia bisnis, secara perilaku atau karakter, begitu rusak dan dikatakan melanggar moral dan juga etika dalam berbisnis. Maka dari itu, penelitian ini membahas pentingnya kewirausahaan bagi anak muda Kristen dalam perspektif Alkitab dan implikasinya terhadap praktik bisnis. Dalam artikel ini, peneliti memakai metode kualitatif melalui sumber-sumber kepustakaan seperti buku-buku, artikel jurnal, Alkitab, dan media internet yang dapat dipertanggungjawabkan juga dengan analisis yang mendalam. Selanjutnya, dengan fokus pada nilai-nilai Alkitab, penelitian ini menyoroti pentingnya mendukung anak muda untuk menjadi wirausahawan. Hasil penelitian menyoroti esensi kewirausahaan dalam perspektif Alkitab yang menekankan pembentukan karakter, pertumbuhan rohani, dan tanggung jawab  Selain itu, entrepreneurship dipandang sebagai panggilan untuk melayani dan memberkati sesama, serta memahami prinsip-prinsip Biblical Entrepreneurship untuk mewujudkan Amanat Agung Tuhan dalam bisnis anak muda Kristen.